Dataset of ecosystem services in Beijing and its surrounding areas - Tianqian Chen; Zhe Feng; Huafu Zhao; Kening Wu (Data in Brief, 2020)
This data article describes the multiple ecosystem services in Beijing and surrounding areas, including grain providing, water yield, carbon sequestration, soil retention, purified water service, cultural services, and habitat quality. These data are mainly from public data sets such as the Harmonized World Soil Database. These data can be used to improve the optimization of human well-being in the social-ecological system and further achieve regional sustainable development. Keywords: Ecosystem service, NDVI, InVEST model, RUSLE, Daily carrying capacity, Beijing and its surrounding areas